Faktor - Faktor yang Mendukung Pemilihan Puskesmas Baki Sukoharjo sebagai Layanan Kesehatan bagi Penderita Hipertensi - Saputri, Rizky Ary; , Supratman, SKM., M.Kes., Ph.D (2017)
The increase in prevalence of cardiovascular disease every year becomes the main problem in the developing and developed countries. According to WHO and ISH (International Society of Hypertension)in Nawi, Arsunan & Jallo (2006) there are 600 million of hypertension patients in all over the world and 3 million of them pass away every year, 7 of 10 patients pass away did not obtain an adequate treatment. Hypertension disease is included in a disease which must be treated routinely and periodically in order not to lead to a complication. Puskesmas (Public Health Center) is the first level of health service that holds their activities comprehensively, integrally and continuously in a society which reside in a certain area. The hypertension patients in an area should use the health service of puskesmas to maintain their health in order that their blood tension is always monitored. The purposes of this research is to know the correlation between the educational level, the knowledge of hypertension, and the individual perception on the health service and the preference of health service in Puskesmas Baki for the hypertension patients. Type of this research is descriptive analytical through a cross sectional approach which was conducted in December 2016 up to January 2017 in Puskesmas Baki of Sukoharjo Muncipality. Sampling was through the technique of accidental sampling which the number of sample was as many as 100 people. The independent variable was the preference of health service, meanwhile, the dependent variables were the educational level, knowledge on hypertension and the individual perception on the health service. The instrument of this research was in the form of questionnaire. The data were analyzed using Chi Square test (α  0.05). In this research, it was obtained the results that: 1) There is no correlation between the educational level and the preference of health service of Puskesmas Baki for the hypertension patients (0.841); 2) There is correlation between the knowledge on hypertension and the individual perception on the health service and the preference of health service of Puskesmas Baki for the hypertension patients (0.001). Suggestions enhance the promotion of existing programs in the Puskesmas (CHC) for patients with hypertension.